Bacteria-mediated tumor immunotherapy via photothermally-programmed PD1 expression. Issue 6 (15th February 2022) - Xu, Wenxuan; Ren, Debao; Yu, Zimeng; Hou, Jia; Huang, Fan; Gan, Tingfang; Ji, Ping; Zhang, Cheng; Ma, Lixin; Hu, Yunhong
Abstract : A thermally-induced bacteria platform was constructed for oncotherapy. E. coli colonized the tumor tissue and form a thrombus. After NIR irradiation, local hyperthermia and heat-induced PD1 inhibit the proliferation and metastasis of tumor cells. Abstract : The special microenvironment of a solid tumor promotes the orientation and colonization of facultative anaerobes. Intratumoral bacterial infection disrupts the local vascular system to form a thrombus, resulting in darkened tumor sites and enhanced near-infrared absorption. Based on this, we constructed thermally-induced bacteria (TIB) to express programmed cell death protein 1 (PD1) at tumor tissue sites. Under laser irradiation, the elevated temperature at the tumor site not only caused damage to tumor cells but also induced the expression of PD1. Expressed PD1 bound to the ligand of PD1 (PD-L1) on the tumor cell surface and facilitated its internalization and reduction, thereby relieving immune suppression in the tumor microenvironment. Through the combined effects of photothermal therapy and immune activation, the ingenious TIB@PD1 approach greatly inhibited the proliferation and metastasis of tumor cells. Therefore, bacteria-based photothermal immunotherapy represents an appealing method for tumor therapy with good specificity and selectivity.